ҚОРАҚАЛПОҚЛАР ЭТНОГРАФИЯСИНИНГ МАҲАЛЛИЙ ТАДҚИҚОТЛАРДА ЁРИТИЛИШИ ҲОЛАТИ (илк босқич) - Абдуллаев, М.А. (SCIENCE and SOCIETY, 2024)
This article provides information about the foundation of Karakalpak ethnography in the Soviet period, conducting expeditions and publishing the first ethnographic studies of the peoples of the country, as well as the beginning of research on the ethnography of the Karakalpak people in the period of independence, their main directions and results.